2011
DOI: 10.1002/app.34093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macromer synthesis time on the properties of the resulting poly(β‐amino ester) degradable hydrogel

Abstract: Poly(b-amino ester) biodegradable hydrogels are common in biomedical applications because of their tunable properties and similarities to natural soft tissue. Previous work has shown property adjustments through the choice of monomers, the ratio between monomers and the addition of a crosslinking component. Here, we show that the reaction time for the creation of the macromer can affect the resulting hydrogel properties, and thus provides another method of tuning properties. Macromer was created through the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…As mentioned previously, a brief macromer synthesis study was carried out to determine the optimal time for the reaction [18]. It is our thought that there is an initial conversion of reactants to products followed by a slower reaction between the macromers to create larger molecular weight molecules.…”
Section: Macromer Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, a brief macromer synthesis study was carried out to determine the optimal time for the reaction [18]. It is our thought that there is an initial conversion of reactants to products followed by a slower reaction between the macromers to create larger molecular weight molecules.…”
Section: Macromer Synthesismentioning
confidence: 99%
“…Macromers were synthesized as outlined previously [3,17,18]. Briefly, the diacrylate and amine were weighed out to meet the desired molar ratios and reacted in a sealed round bottom flask maintained at 85°C.…”
Section: Macromer Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…20,32 To review, polyethylene glycol (PEG) 400 diacrylate (Polysciences, Inc., Warrington, PA) and isobutylamine (Sigma-Aldrich, St. Louis, MO) were combined in a 1.2:1 molar ratio and placed in a flask partially submerged in a silicon oil bath pre-heated to 85°C. The reaction mixture was continuously stirred for 48 hr and then removed from the heat.…”
Section: Methodsmentioning
confidence: 99%
“…3133 In particular, the poly(β-amino ester) (PBAE) family of hydrogels has properties that are easily tuned to achieve great control as a drug delivery vehicle. 32,34,35 Previous research has shown that PBAE particles can be homogeneously embedded into a CS matrix, which may allow further control over the release of drug from these particles as the CS matrix erodes. 20 …”
Section: Introductionmentioning
confidence: 99%